The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1172/jci107381
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Human Prolactin Secretion by Intravenous Infusion of L-Tryptophan

Abstract: A B S T R A C T Previous studiesThese results support the concept that the effect of L-tryptophan on the secretion of human prolactin is mediated through its conversion to serotonin and are consistent with reported experimental observations that serotonin may participate in the reciprocal regulation of prolactin and gonadotropins. INTRODUCTIONRecent studies on human prolactin have indicated the primary importance of hypothalamic mechanisms in the regulation of secretion of this hormone by the pituitary (1-3). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(42 citation statements)
references
References 24 publications
3
39
0
Order By: Relevance
“…19,20 The secretion of prolactin is regulated by 5-HTergic mechanisms in the brain. 322,323 Therefore, increased plasma prolactin can be interpreted as an index of enhanced brain serotonin function 324,325 and hypersensitivity of the 5-HTergic system. 326,327 Neuroendocrine responses to 5-HT agonists are an indication of postsynaptic receptor sensitivity, with relatively high hormonal responses being indicative of receptor hypersensitivity while relatively low hormonal responses suggest receptor hyposensitivity.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 99%
“…19,20 The secretion of prolactin is regulated by 5-HTergic mechanisms in the brain. 322,323 Therefore, increased plasma prolactin can be interpreted as an index of enhanced brain serotonin function 324,325 and hypersensitivity of the 5-HTergic system. 326,327 Neuroendocrine responses to 5-HT agonists are an indication of postsynaptic receptor sensitivity, with relatively high hormonal responses being indicative of receptor hypersensitivity while relatively low hormonal responses suggest receptor hyposensitivity.…”
Section: Experimental Manipulations Of 5-ht In Relation To Sv Factorsmentioning
confidence: 99%
“…Serotonin has also been involved in the neuroregulation of PRL secretion in mammals (Maclndoe and Turkington, 1973;Kato et al" 1974). Trazodone [2-3-4(m-chlorophenyl)-lpiperazinyl-propyl-s-triazol-4-3-a-piridyn-3-(2H)-one], employed in the treatment of anxiety and depressive states (Silvestrini etal., \968\Banand Lehman, 1973;Saarma, 1974), seems to in teract with the serotoninergic system in some experimental models (Garattini et al, 1976).…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that the systemic administration of L-tryptophan, a precursor of 5-hydroxytryptophan (5-HTP), or 5-HTP, a precursor of serotonin, raised plasma prolactin levels both in rats (Lu and Meites, 1973) and in man (Kato et al, 1974c;Maclndoe and Turkington, 1973). The intraventricular injection of serotonin also stimulates prolactin release (Kamberi et al, 1971a).…”
mentioning
confidence: 99%